XML. NET developer's guide - Sills, Adam. (Rockland, Mass : Syngress, 2002)
Compete with the big players in today's E-commerce marketplace Electronic Data Interchange (EDI) has long been the standard for large business enterprises to communicate in the B2B marketplace. However, EDI is a difficult technology - the cost and support of EDI standards is often too much for a small or medium business enterprise to bear. To compete in the current E-commerce marketplace, many organizations are beginning to take an interest in the interoperability that exists between XML (Extensible Markup Language) and EDI. XML .NET Developers Guide is written for information technology professionals responsible for supporting data management in both small and large organizations. This book appeals to both individuals working with an existing EDI environment, and small to medium businesses looking to increase their market presence by competing with current EDI players using XML/EDI. XML/EDI is quickly becoming an industry standard, however there is a noticeable lack of quality reference material for programmers looking to adopt these standards. You can take it with you. The book comes with Syngress' revolutionary Wallet CD containing a printable HTML version of the book, all of the source code, and demo versions of popular XML/EDI translation tools Up to the minute web-based support with solutions@syngress.com.
Introducing the Microsoft .NET framework -- Visual Studio.NET IDE -- Reviewing the fundamentals of XML -- Using XML in the .NET framework -- Understanding .NET and XML security -- Web development using XML and ASP.NET -- Creating an XML.NET guestbook -- Creating a message board with ADO and XML -- Building a remote database viewer -- Building a wholesale catalog.
Includes index.
Keywords: Electronic data interchange; XML (Document markup language); Client/server computing; Electronic books